PENGARUH MOTIVASI DAN KEPUASAN KERJA PEGAWAI TERHADAP KUALITAS LAYANAN ADMINISTRASI AKADEMIK DI FTIK IAIN PALU - Wiwin Mistiani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
This study aims to determine: 1) The effect of employee work motivation on the quality of academic administration services in FTIK IAIN Palu. 2) The effect of employee job satisfaction on the quality of academic administrative services in FTIK IAIN Palu., 3). Effect of Motivation and Job Satisfaction of employees on the Quality of Academic Administrative Services in FTIK IAIN Palu. This research uses a quantitative approach with questionnaire data collection techniques, questionnaires, interviews, observation, and documentation. While the data analysis technique used is the classic assumption test using normality, multicollinearity, and heteroscedasticity tests. Research Results Show There is a significant influence on the work motivation of administrative employees on the quality of Academic Administration Services by 17.4%. There is a significant effect of Employee Job Satisfaction on Academic Administration Service Quality of 51%, and There is a significant effect of motivation and level of employee job satisfaction the quality of academic administration services is 80.3%. Keywords: motivation, satisfaction, administrative services